Double play - Green, Tim, 1963-; Jeter, Derek, 1974- (Green, Tim, 1963- Baseball genius, 2019)
When New York Yankee James "JY" Yager strikes out on his own to show he can still hit in the majors without the help of twelve-year-old Jalen's baseball genius, Jalen focuses on his own baseball career as he tries to carve out a spot with the Rockton Rockets. But when things go wrong for both of them, they will have to work together to pull off the biggest double play of their careers.